Looking ahead: long-term prospects for Africa's agricultural development and food security - Rosegrant, Mark W.; Cline, Sarah A.; Li, Weibo; Sulser, Timothy B.; Valmonte-Santos, Rowena (International Food Policy Research Institute, 2005)
Sub-Saharan Africa is the only developing region in the world where food insecurity has worsened instead of improved in recent decades. In this discussion paper, Mark W. Rosegrant, Sarah A. Cline, Weibo Li, Timothy B. Sulser, and Rowena A. Valmonte-Santos show that this discouraging trend need not be a blueprint for the future. The research contained in this discussion paper was conducted in preparation for the IFPRI 2020 Africa conference “Assuring Food and Nutrition Security in Africa by 2020: Prioritizing Actions, Strengthening Actors, and Facilitating Partnerships,” held in Kampala, Uganda, April 1–3, 2004. The authors examine the implications of several different policy scenarios based on IFPRI’s International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT). This model, developed at IFPRI in the early 1990s, has been continually updated to incorporate more food sectors and geographic regions. In this paper, the authors use IMPACT to assess the consequences of a wide range of policy and investment choices for Africa, including a business as usual scenario (continuation of current policy and investment trends through 2025), a pessimistic scenario (declining trends in key investments and in agricultural productivity), and a vision scenario (improving trends in investments and hence in agricultural productivity and human capital), as well as scenarios for more effective use of rainfall in agriculture, reduced marketing margins, and three different scenarios for trade liberalization. The wide variation in results reveals how much these choices will matter. For example, the number of malnourished children under five years old in Sub-Saharan Africa in 2025 is projected to be 38.3 million under business as usual, 55.1 million under the pessimistic scenario, and 9.4 million under the vision scenario. It is our hope that this research will clarify the steps needed to help stimulate the actions contributing to approaching the vision scenario.